Context matters: A meta-ethnography investigating barriers and facilitators for the effective implementation of gambling harm prevention and reduction policies - Jani Selin; Lauri Kauppila (PLoS ONE, 2026)
This meta-ethnography investigates how contextual factors influence the implementation and effectiveness of gambling harm prevention and reduction interventions. Despite growing recognition of gambling as a public health concern, many interventions focus on individual responsibility and lack evidence of effectiveness. This study synthesizes qualitative research to examine how social, institutional, and cultural contexts shape seven intervention types: educational campaigns, exclusion programs, availability regulations, spending limits, advertising restrictions, behavioral feedback, and behavioral interruptions. A systematic literature search was conducted across multiple databases (Medline, PsycINFO, SocINDEX, Applied Social Sciences Index and Abstracts, Worldwide Political Science Abstracts, Web of Science, and Google Scholar). A quality appraisal using the CASP checklist identified eight methodologically weak or low-quality studies, which were excluded from the synthesis. Fifty-one peer-reviewed qualitative studies were reviewed, with 37 included in the final synthesis. The findings highlight a core tension between harm prevention and reduction goals and the financial imperatives of gambling revenue. Interventions are variably perceived and implemented depending on context and framing. A lines-of-argument synthesis was used to develop an interpretation across the interventions, indicating that system-level interventions are often weakened by the economic interests of governments and the gambling industry, while individual-level interventions shift responsibility onto gamblers and staff, often resulting in limited effectiveness and unintended consequences such as migration to alternative gambling products. Limited high-quality studies per intervention, few focused on online gambling, and regional bias may affect transferability. This review underscores the need to reframe gambling harm as a systemic issue and to develop context-sensitive public policies that are clearly communicated to target populations. Effective prevention requires countering the gambling industry’s framing, which individualizes responsibility, resists regulation, and justifies availability on economic grounds, through strategies integrating systemic regulation, digital prevention tools, and harm-reduction. Policymakers should examine interventions and their assumptions, placing public health above gambling revenue.